2020
DOI: 10.1177/0022042620917103
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Stimulant Diversion on a College Campus: Intrapersonal, Interpersonal, and Environmental Correlates

Abstract: Prescription stimulant diversion is a behavior that increases the availability and accessibility of prescription stimulants for purposes such as misuse. As such, we aimed to develop a theory-guided understanding of diversion correlates. Data are from a probability sample of 499 undergraduate college students attending one California university. Participants completed a 100-item survey related to prescription stimulant misuse and diversion. We first calculated prevalence of diversion and associations with demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…The primary source of diverted medication was family and friends, while most of the medication that was diverted was given or shared rather than purchased. Diversion is a public health concern because it is invisible (Garcia et al, 2022; Lam et al, 2020; Lasopa et al, 2015), and yet must be balanced with the recognized need and medical benefit of prescription stimulants. Most IN users reported performance enhancement as their primary reason for NMU (Compton et al, 2018; Faraone et al, 2020; Wilens et al, 2008), however, a sizeable proportion of IN users reported IN use to get high or to “party longer.” An interaction between route of administration and motivation for use has been recently reported in other literature and bears further examination to better characterize this relationship (Vosburg, Robbins et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The primary source of diverted medication was family and friends, while most of the medication that was diverted was given or shared rather than purchased. Diversion is a public health concern because it is invisible (Garcia et al, 2022; Lam et al, 2020; Lasopa et al, 2015), and yet must be balanced with the recognized need and medical benefit of prescription stimulants. Most IN users reported performance enhancement as their primary reason for NMU (Compton et al, 2018; Faraone et al, 2020; Wilens et al, 2008), however, a sizeable proportion of IN users reported IN use to get high or to “party longer.” An interaction between route of administration and motivation for use has been recently reported in other literature and bears further examination to better characterize this relationship (Vosburg, Robbins et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to diversion, another study that surveyed college students with a prescription found that 43.8% had diverted their prescription stimulant medication (Schultz et al, 2017). In a more recent study, Lam and colleagues (2020) reported that diversion is not limited solely to students with a prescription, indicating that the sub-population of students engaging in these behaviors is greater than previously considered. As prescription stimulant misuse and diversion represent interrelated substance use behaviors, and emerging adulthood has been noted as a period when the prevalence of substance use is highest (Arnett, 2005), then it is understandable that a systematic review of 111 studies found misuse and diversion to disproportionately affect college-attending emerging adults (Faraone et al, 2020).…”
Section: Introductionmentioning
confidence: 94%
“…From a developmental perspective, if emerging adulthood is viewed as a period of identity explorations (Arnett, 2005), students with high levels of exploration should engage in more misuse and diversion as compared to students with lower levels of exploration. Indeed, prior research has shown that students who view college as a time to experiment with drugs, and students who endorse the characteristics of a sensation-seeking personality, engage in more frequent prescription stimulant misuse and diversion (e.g., Bavarian et al, 2013; Lam et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in one study with college students who have a prescription for stimulant medications, the prevalence of past-year misuse and diversion was 33% and 18%, respectively (Ramachandran et al, 2020). In a separate study including students with and without a prescription, the prevalence of having ever misused or diverted during college was approximately 21% (Bavarian et al, 2018) and 10% (Lam et al, 2020), respectively. These levels of diversion are particularly problematic because when friends and/or acquaintances serve as the primary source of prescription stimulants (Garnier-Dykstra, Caldeira, Vincent, O'Grady, & Arria, 2012), the oversight provided by health care providers is lacking, thereby increasing the chance for adverse effects (Goldsworthy, et al, 2008).…”
Section: Introductionmentioning
confidence: 99%